Re-Examining the Role of Implicit Implications in Jurisprudential Inference - Morteza Nowrozi; Abbas Ali Soltani; Hossein Naseri (مطالعات فقه اسلامی و مبانی حقوق, 2024)
The inference of jurisprudential rules is directly related to the way their evidence is implied. Among the indications, “implicit implication” is very important considering that it has many types. The upcoming research is trying to answer the basic question that how many types of implicit implication play role in deriving a Sharia ruling? By studying and exploring the sources and processing them in a descriptive and analytical way, these results were obtained: More than seven types of implicit implication play role in jurisprudential inference. Presenting detailed cases of jurisprudence proves the importance and role of these indications in deriving Sharia rulings and the lacuna of assigning and determining a place for the discussion of such implications in the discussion of Sharia arguments. Proposing a new plan to compensate for this gap is one of the other achievements of this research.